MENGUPAYAKAN KEMBALI EKSISTENSI IDEOLOGI PANCASILA - Efriza Efriza (Populis : Jurnal Sosial dan Humaniora, 2018)
ABSTRACTThis paper attempts to analyze the development of thinking and also responds to efforts to re-establish the existence of Pancasila Ideology as a common ideology. The government's efforts also demonstrate the shared desire of nationalism, democracy, and the ideology of Pancasila together. Pancasila ideology's unconscious awareness is an attempt to foster a sense of nationalism. Keywords: Pancasila Ideology, Nationalism, Democracy,